Pengaruh metode variasi latihan terhadap kekuatan otot kaki dan kontribusinya terhadap peningkatan hasil smash bola voli - Mahmuddin, Mahmuddin; D. Sihombing, R. Syaifullah; Yunis Bangun, Sabaruddin; Josua Hamonangan, Dian (Universitas Nusantara PGRI Kediri, 2024)
This research is based on the contribution of leg muscle strength to the results of volleyball smashes. So, it is necessary to increase strength through a training program to produce good smash results. This study aimed to determine the effect of burpee exercise variations on increasing leg muscle strength and volleyball smash results. This research method is a quasi-experimental research design experiment with a pretest-posttest. The subjects involved in this study were male volleyball players of North Sumatra Club, with purposive sampling and subject collection techniques, the total subjects involved amounted to 10 players. The instrument used in this study is leg muscle strength using the vertical jump test, which is usually done to determine the strength of the leg muscles or an athlete's explosive power while measuring smashing skills for fast and targeted target attacks using Lavage's smash skill test instructions. Analysis of research data Analysis of data using statistical formulas to prove whether the hypothesis data that has been proposed is accepted or rejected by the Liliefors test. Based on the results of the calculations, the hypothesis is that vertical jump = 6.026> 1.859, so burpee training variations significantly influence leg muscle strength. Smash results, hypothesis obtained count smash results = 8.664 ttable> 1.859, So there is a significant influence of burpee training variations on the smash. This study concludes that burpee variation exercises can be an alternative to increase leg muscle strength and volleyball smash results.